Comfort experience in palliative care: a phenomenological study - Coelho, Adriana (2016)
Palliative care aims to provide maximum comfort to the patient. However it is unknown what factors facilitate or hinder the experience of comfort, from the perspective of inpatients of palliative care units. This lack of knowledge hinders the development of comfort interventions adjusted to these patients. The aim of this research is to describe the comfort and discomfort experienced by inpatients at palliative care units.